THE ROLE OF PHOSPHATES IN AGRCICULTURE AND HIGHLIGHTING KEY ISSUES IN AGRICULTURE FROM THE PERSPECTIVE OF CLIMATE CHANGE - Popescu, Lavinia; Safta, Adela Sorinela (Economics of Agriculture, 2021)
This paper investigates in the foreground the state of agricultural systems in interdependence with climate change, a condition synec vanon of decarbonization of agriculture. The relationship between ecologically responsible agricultural systems places the innovative design of agricultural processes as the first factor in achieving the success of environmental responsibilities in addressing any agricultural processes customized to the area through the symbiosis between production in order to protect the biosphere. Thus, the constraints of reducing the consumption of chemical fertilizers in agriculture have gained new value at the same time as the interest of producers to gradually comply with the new more sustainable environmental requirements by optimizing synergies in the vision of the Common Agricultural Policy (CAP). The paper also identifies the risks of degradation of natural resources as an effect of environmental change, such as phosphorus, a much-needed element in agriculture, a declining global re source. From the empirical analysis of the analyzed sources we followed on the basis of statistical data a calibration of the risk trends generated by the impact of the adaptability of agriculture to environmental requirements, in achieving an agriculture designed for sustainability.